Adaptive behaviour in children exposed to topiramate in the womb: An observational cohort study. (February 2023) - Knight, R.; Craig, J; Irwin, B; Wittkowski, A.; Bromley, R.L.
Highlights: Prenatal topiramate exposure was associated with poorer adaptive behaviour outcomes. An increased risk of autistic spectrum disorder was seen in this small cohort. Further work is urgently required to understand topiramate's risk profile. Abstract: Objective: Many women with epilepsy need to continue anti-seizure medications (ASMs) throughout pregnancy. The current study investigated adaptive behaviour outcomes in children exposed to topiramate in the womb. Method: An observational, cross-sectional study was designed, recruiting mother-child-pairs from the UK Epilepsy and Pregnancy Register (UKEPR). Health, developmental histories and Vineland Adaptive Behaviour Scale-Third Edition (VABS-III) assessments were administered via telephone by a blinded researcher, supplemented with prospectively collected pregnancy and medication information. Topiramate monotherapy exposed children were compared to VABS-III normative data as recruitment was disrupted by the COVID-19 pandemic. Results: Thirty-four women with epilepsy from 135 (25%) initially agreed to participate in the study, of whom 26 women completed telephone interviews about their children ( n  = 28). Children ranged from 2.5 to 17 years of age at the time of assessment. Six topiramate-exposed children were born small for gestational age, and there were significant associations between birthweight, dose and VABS-III scores. Significantly lower scores were observed in topiramate-exposed children ( n  = 21) with a significant dose-response relationship established after adjustment for parental educational level. Daily mean dosage was 280.21 mg, with high dosages of topiramate associated with a 12-point reduction in VABS-III scores. Additionally, four topiramate-exposed children (19.05%) had diagnoses of Autism Spectrum Disorder, which was significantly higher than UK prevalence rates (1.1%). Conclusions: The findings of poorer adaptive behaviour, higher incidence of ASD and associations with birth weight are of concern and require further validation and replication using larger prospectively-recruited samples and comparator cohorts. Implications for research and clinical practice are discussed.